Evaluation level of cognitive, affective and psychomotor in extension programme planning through empowerment approach of Universiti Putra Malaysia students - Mohammad Daud, Siti Nadzirah (2018)
Extension programmed planning is a process of situation, objectives, problems, and solutions which has been prepared on the basis of an adequate and systematic planning effort and which forms the basis of extension teaching activities in a specific area, for a given period. In agriculture, it is important to make sure among farmer uses the latest technology. Unfortunately, nowadays many extension agents do not develop and use their knowledge and skill effectively for farmers to be used through human resource development and technology transfer. Therefore, objectives for this study are (1) to evaluate the level of cognitive, affective, and psychomotor of students in extension programs planning through empowerment approach of class TKP3201 and TKP4203 semester 1 and 2 in the year of 2016/2017; (2) to study the the relationship between cognitive, affective and psychomotor with students’ performance through empowerment approach among students; and (3) to compare the level of cognitive, affective, and psychomotor of students in extension programs planning through empowerment approach between both of semester. 153 students participate as respondents which are 112 students for semester 1 and 41 students for semester 2. Quantitative Method uses questionnaire design using a Likert scale. SPSS 23 and independent t-tests analysis were used for data analysis. The performance of students agriculture extension showed that no different for the level of cognitive, affective, and psychomotor of students in extension programs planning between these classes in semester 1 and 2, UPM.